RISK STRATIFICATION AND PROGNOSIS OF CARDIOVASCULAR DISASTERS IN THE POPULATION IN A FAMILY POLYCLINIC (Eureka Journal of Health Sciences & Medical Innovation, 2026)
A set of traditional and specific risk factors in the population has been studied. Independent predictors of high cardiovascular risk have been identified. A logistic model of risk forecasting in the population with high accuracy (AUC=0.83) has been built.
Keywords: Cardiovascular risk; monitoring; ROC analysis; model of prognosis, arterial hypertension, type 2 diabetes mellitus.